Development and in vitro Profiling of Dual FXR/LTA4H Modulators. (24th May 2021) - Schierle, Simone; Brunst, Steffen; Helmstädter, Moritz; Ebert, Roland; Kramer, Jan S.; Steinhilber, Dieter; Proschak, Ewgenij; Merk, Daniel
Abstract: Designed polypharmacology presents as an attractive strategy to increase therapeutic efficacy in multi‐factorial diseases by a directed modulation of multiple involved targets with a single molecule. Such an approach appears particularly suitable in non‐alcoholic steatohepatitis (NASH) which involves hepatic steatosis, inflammation and fibrosis as pathological hallmarks. Among various potential pharmacodynamic mechanisms, activation of the farnesoid X receptor (FXRa) and inhibition of leukotriene A4 hydrolase (LTA4Hi) hold promise to counteract NASH according to preclinical and clinical observations. We have developed dual FXR/LTA4H modulators as pharmacological tools, enabling evaluation of this polypharmacology concept to treat NASH and related pathologies. The optimized FXRa/LTA4Hi exhibits well‐balanced dual activity on the intended targets with sub‐micromolar potency and is highly selective over related nuclear receptors and enzymes rendering it suitable as tool to probe synergies of dual FXR/LTA4H targeting. Abstract : Polypharmacology by design : FXR agonists (FXRa) and LTA4H inhibitors (LTA4Hi) hold therapeutic potential in non‐alcoholic steatohepatitis (NASH). We report the design and characterization of a potent FXRa/LTA4Hi with balanced dual activity and high selectivity over related transcription factors and enzymes. It may serve as a pharmacological tool to evaluate potential synergies of dual FXR/LTA4H modulation in NASH.